Family adoption program (FAP) as a learning tool—perceptions of students and faculty of community medicine - Rajyalakshmi Chepuru; Kuppli Sai Sushma; Sarada Vadlamani; Rongala V. Manasa; Bodhi Srividya Vennam (Journal of Family Medicine and Primary Care)
Introduction: The family adoption program, a newer initiative in the medical education curriculum, provides a learning opportunity toward community-based health care to Indian Medical Graduates. However, it has its own challenges and opportunities. The Objective of the study is to understand the perceptions of faculty and students regarding this program. Material and Methods: A descriptive cross-sectional study was done among the faculty of Department of Community Medicine and phase 1 medical undergraduates of the selected medical colleges. A pretested semi-structured questionnaire was administered in Google Forms. The responses received from the participants in Google Forms were retrieved and analyzed using MS Excel and SPSS version 25. Results: About 48 faculty of designation ranging from senior resident to professor participated in the study. A total of 190 students in phase 1 MBBS participated in the study. Out of 150 students, 86 (44%) were from private medical colleges and 104 (55%) were from government medical colleges. The perception of the faculty and students regarding FAP was taken in a Likert scale. Most of them agreed that it is a good academic tool to learn communication skills, identify health problems in the community and various determinants of health, develop creative thinking and reasoning. The faculty mentioned that they faced challenges in arranging logistics. The faculty also made some recommendations to improve the program. Conclusion: The current study showed despite the challenges faced during the implementation of the FAP program, it will empower the students and faculty for better training, community-oriented research, and community-oriented medical education in the long run.